Relationship Between Bone Mineral Density and Disease Activity in Patients with Ankylosing Spondylitis - Hasan Ulusoy; Ayhan Bilgici; Ömer Kuru; Nebahat Sarıca; Şule Arslan; Ünal Erkorkmaz (Archives of Rheumatology, 2010)
Objective: This retrospective study was planned to determine the relationship between bone mineral density (BMD) and clinical, radiological and laboratory parameters in patients with ankylosing spondylitis (AS). Materials and Methods: The study group consisted of 28 patients with a mean disease duration of 11.9±6.1 years. In addition to clinical and demographic variables, lumbar and femoral BMD were evaluated with dual energy X-ray absorbtiometry. Lumbar spine score (LSS) and sacroiliac score (SIS) were calculated by grading of standard radiographs. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) level were determined as laboratory parameters. Results: The rate of osteoporosis and osteopenia were 7.1% and 25% at the lumbar spine, and 14.2% and 17.8% at the femoral neck, respectively. LSS was significantly correlated with lumbar BMD (r=0.70, p<0.001), but not with femoral neck BMD (r=-0.11, p=0.55). SIS was negatively correlated with femoral neck BMD (r=-0.79, p<0.001), but not correlated with lumbar BMD (r=0.19, p=0.32). While lumbar BMD was positively correlated with disease duration (r=0.37, p=0.05), femoral neck BMD showed negative correlation with disease duration (r=-0.46, p=0.01). The evaluation of clinical paramaters and BMD showed that morning stiffness, spinal pain, ESR and CRP were not correlated with BMD. Only modified Schober’s test was related to BMD on both lumbar spine and femoral neck. Conclusion: Ankylosing spondylitis patients are at risk for developing osteoporosis. In advanced disease, the lumbar BMD is misleadingly high because of paravertebral calcification and ossification. Therefore, it is more rational to evaluate the BMD at the femoral neck. (Turk J Rheumatol 2010; 25: 24-8)